Trade regulations:Sell, sell, sell - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Goodbye import duties. Farewell quotas. Hello rules. Trade in agricultural products from ACP countries now has to comply with complex new rules, often about quality. We look at how to jump the latest barriers.With world trade now liberalised under...